Brand valuation model - Ginevičius, Romualdas; Gudačiauskas, Darius (Journal of Business Economics and Management, 2004)
Brand valuation technique is a core problem in a company value creation process. It has been done a lot of researches on the issue since brand valuation hit the headlines in 1988. The main task in brand valuation is to distinguish brand earnings from the earnings attributable to another assets: patents, intellectual property, and tangible assets. This seems to be an undisputable must, but not the only task for brand valuator. Another task is to estimate probability that the brand will generate these earnings in the future. Aim of our article is to propose brand earnings calculation, brand index calculation and brand risk assessment models, which are the results of the final doctoral dissertation. We believe that we have developed an ideal brand valuation model for emerging markets with low share liquidity. First Published Online: 14 Oct 2010